2019
DOI: 10.3390/cells8121498
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Controlled by the Alternative Splicing Factor Nova2 in Endothelial Cells

Abstract: Alternative splicing (AS) plays an important role in expanding the complexity of the human genome through the production of specialized proteins regulating organ development and physiological functions, as well as contributing to several pathological conditions. How AS programs impact on the signaling pathways controlling endothelial cell (EC) functions and vascular development is largely unknown. Here we identified, through RNA-seq, changes in mRNA steady-state levels in ECs caused by the neuro-oncological ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…By regulating splicing, NOVA2 determines vascular morphogenesis and endothelial biology 22 . Inspecting the knowledge associated with the listed genes by OT showed that many of the genes (Table 3) contributed to the genetic basis of physical measurements (e.g., BMI), brain and eye measurements.…”
Section: Gene-based Associations Using Skat and Pwas Analysesmentioning
confidence: 99%
“…By regulating splicing, NOVA2 determines vascular morphogenesis and endothelial biology 22 . Inspecting the knowledge associated with the listed genes by OT showed that many of the genes (Table 3) contributed to the genetic basis of physical measurements (e.g., BMI), brain and eye measurements.…”
Section: Gene-based Associations Using Skat and Pwas Analysesmentioning
confidence: 99%
“…Consistently, nova2 zebrafish mutants present many vascular defects [ 184 ]. NOVA2 modulates AS of genes involved in EC cytoskeleton organization and cell-cell adhesion, as well as the transcription factors PPAR-γ and E2F Dimerization Partner 2 (Tfdp2) [ 187 ]. Very recently NOVA2 was shown to modulate AS of components of Mapk/Erk pathway during lymphatic EC specification [ 186 ].…”
Section: Main Textmentioning
confidence: 99%
“…A number of EC-specific RBFOX2 splicing targets encode for ECM components or factors involved in cell adhesion, cell cycle, cytoskeletal remodeling and immune response [ 31 ]. Similar to NOVA2 [ 184 , 187 ], RBFOX2 also regulates the abundance of mRNAs transcribed from genes that belong to the same GO categories [ 31 ], suggesting that similar biological processes could be modulated by RBFOX2 in ECs through both transcriptional and post-transcriptional mechanisms.…”
Section: Main Textmentioning
confidence: 99%
“…The current knowledge on the role of AS during vascular development and angiogenesis is still limited. The Neuro-oncological ventral antigen 2 (NOVA2) is a tissue-restricted SRF expressed by ECs of the blood vessels where it orchestrates vascular morphogenesis 27 29 and lymphatic EC specification 30 . NOVA2 is involved in multiple diseases.…”
Section: Introductionmentioning
confidence: 99%